KUALITAS PELAYANAN ADMINISTRASI BAGI PASIEN PEMEGANG KARTU BPJS DI RUMAH SAKIT UMUM KABUPATEN KARIMUN - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
This study aims to analyze the level of quality of administrative services for BPJS card holders in the General Hospital of Karimun District. The results of the study based on the quality dimension consisting of: Tangibles (direct evidence), patients stated that the officers in providing services were quite good with neat and polite clothing. Physical facilities such as waiting rooms are quite comfortable, queues are very organized, thus speeding up the service process. Reliability is quite good ie the patient is easy and the administration process is not complicated. Responsiveness (responsiveness) of employees to criticism and patient complaints, responded properly and immediately followed up. Besides that, employees are present at the service office on time, so that if there are patients who come directly served well. Assurance (discipline) is discipline, courtesy and friendliness of employees is quite good as evidenced by the patients who come welcomed by the employees to ask things they can help. Empathy of employees which includes attention to patients who come to the administration for patients BPJS card holders ask the needs of patients and provide explanations that are easily understood by the community at large.